KEBIJAKAN PENYIDIKAN TINDAK PIDANA PENGUSAHAAN AIR BAWAH TANAH DI DITRESKRIMSUS POLDA JATENG - Endah Puji Lestari; Maryanto Maryanto (UNISSULA Semarang, 2017)
This study menaganalisa policy of investigation of criminal act of underground water concession in Ditreskrimsus Polda Jateng. The purpose of this study are : 1. To find out the investigator's policy in conducting an investigation of current underground water utility. 2. To know the criminal law policy in the investigation of future underground water utility.The result of the research : Hotel New Puri Garden (PT. AGUNG ASRI JAYA) Semarang conducting the operation of water resources in the form of groundwater extraction is not equipped with permission, violate : Article 11 paragraph (2) RI Law No. 11 of 1974, Article 15 paragraph (1) Sub-Paragraph b of the Law of the Republic of Indonesia No. 11 Year 1974, Article 34 paragraph 1 letter b of Government Regulation no. 121 Year 2015. In connection with this, it is expected that the Governor of Central Java and DITRESKRIMSUS POLDA JATENG can coordinate and calculate the impact in the long term. Keywords : Criminal Law Policy, Crime of Underground Water Utilization.